Fabrication and Performance Evaluation of Rice Polishing Machine - Win, Thida; Win, Htay Htay; Latt, Aung Ko (The Indonesian Journal of Computer Science, 2024)
This paper focuses on the fabrication and performance evaluation of rice polishing machine. The motor power of the machine is 1.5 hp and rotational speed is 1440 rpm. This motor uses v-belt transmission system to drive the main shaft and blower shaft. The number of two belts are used in this transmission system. The diameter of the main shaft is 22mm. ASME code equation is used to design the main shaft for rice polishing machine. Square key is used and shear and torsional strength of the key are 58.5404MPa. Single-row deep groove ball bearing is selected for left and right bearing of main shaft. The average milling efficiency, broken efficiency and milling capacity and moisture contents for existing and modified blade were compared. The average milling capacity is 35.23 kg/h, 38.41 kg/h and 41.76 kg/h with modified blade and 30.35 kg/h, 32.20 kg/h and 34.03 kg/h with existing blade at the moisture condition of 13%, 12% and 11%, respectively. As comparison results, the modified blade of the machine has more efficient and convenience than the existing blade of the machine.